THE ROLE OF GREEN HUMAN RESOURCE MANAGEMENT – AN ASSESSMENT - Yadav, Anuja; Jindal, Lokesh; Verma, Rajanikant; Vishwakarma, Komal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose- Green human resource management (HRM) aims to influence employee behavior so businesses can meet their environmental objectives. Businesses can apply the Green HRM idea to every HRM function. This paper reviews 18 Scopus-indexed articles to highlight how Green HRM is integrated into various HRM tasks and to examine the impacts that Green HRM offers to individuals and different organizations. Methodology—This study utilized the PRISMA flowchart to examine the effects of green HRM on individuals and organizations. In order to analyze the secondary data, a TCCM approach is used, which allows the researchers to obtain comprehensive and insightful information. Findings—The outcomes showed that the organization as a whole and individual employees benefited from the adoption of Green HRM. Enhancing resource efficiency, building a favorable company image, and improving economic and environmental performance were some of the benefits of implementing Green HRM at the organizational level.Additionally, it produced an eco-friendly workplace culture and atmosphere within the firm. Originality/Value- The study deepens our understanding of green human resource management (HRM) practices. Green HRM approaches, such as green performance management, positively and significantly impact employees’ pro-environmental views, encouraging green actions in organizations.